2017
DOI: 10.1371/journal.pone.0184718
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diverse viruses in upper respiratory samples in dromedary camels from United Arab Emirates

Abstract: Camels are known carriers for many viral pathogens, including Middle East respiratory syndrome coronavirus (MERS-CoV). It is likely that there are additional, as yet unidentified viruses in camels with the potential to cause disease in humans. In this study, we performed metagenomic sequencing analysis on nasopharyngeal swab samples from 108 MERS-CoV-positive dromedary camels from a live animal market in Abu Dhabi, United Arab Emirates. We obtained a total of 846.72 million high-quality reads from these nasoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Our search found that dromedary populations in 16 countries have been tested for MERS-CoV RNA, 13 of which report positive results indicating active infection. These include KSA (0.12-56%) (45, 46, 49-51, 70), UAE (0-29% (6266) or 0-100% if dromedaries epidemiologically linked to human MERS-CoV cases are included(6769)), Qatar (22-79%) (15, 58, 71, 72), Oman (7%) (55), Iraq (15%) (34), and Jordan (62%) (39), as well as Egypt (4-15%) (27, 29, 30), Ethiopia (10%) (23), Kenya (0.35-0.95%) (43, 44), Nigeria (3-11%) (53, 54), Burkina Faso (5%) (23), Morocco (2%) (23), and Pakistan (3%) (57). See Fig 4 for a map of RNA prevalence, and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our search found that dromedary populations in 16 countries have been tested for MERS-CoV RNA, 13 of which report positive results indicating active infection. These include KSA (0.12-56%) (45, 46, 49-51, 70), UAE (0-29% (6266) or 0-100% if dromedaries epidemiologically linked to human MERS-CoV cases are included(6769)), Qatar (22-79%) (15, 58, 71, 72), Oman (7%) (55), Iraq (15%) (34), and Jordan (62%) (39), as well as Egypt (4-15%) (27, 29, 30), Ethiopia (10%) (23), Kenya (0.35-0.95%) (43, 44), Nigeria (3-11%) (53, 54), Burkina Faso (5%) (23), Morocco (2%) (23), and Pakistan (3%) (57). See Fig 4 for a map of RNA prevalence, and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in previous studies, the authors aimed to establish nine genera within the family Genomoviridae based on pairwise comparisons of complete genome sequences [70]. CRESS DNA viruses, including genomoviruses, have been found in association with a great variety of animal species, such as camels [98], bats [89], mongooses, badgers [99], wolves [100], pigs [101], and humans [102], as well as in environmental-associated [103] and plant-associated [104] samples. However, no direct implication with a disease has been demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Our search found that dromedary populations in 16 countries have been tested for MERS-CoV RNA, 13 of which report positive results indicating active infection. These include KSA (0.12-56%) (Alagaili et al, 2014;Khalafalla et al, 2015;Sabir et al, 2016;Alfuwaires et al, 2017;Kasem et al, 2018a, b), UAE (0-29% (Wernery et al, 2015a, b;Yusof et al, 2015;Li et al, 2017;Yusof et al, 2017) or 0-100% if dromedaries epidemiologically linked to human MERS-CoV cases are included(Al Hammadi et al, 2015;Muhairi et al, 2016;Paden et al, 2018)), Qatar (22-79%) Reusken et al, 2014a;Farag et al, 2015;Mohran et al, 2016), Oman (7%) (Nowotny and Kolodziejek, 2014), Iraq (15%) (Al Salihi and Alrodhan, 2017), and Jordan (62%) (van Doremalen et al, 2017), as well as Egypt (4-15%) , Ali et al, 2017a, Ethiopia (10%) (Miguel et al, 2017), Kenya (0.35-0.95%) (Kiambi et al, 2018;Ommeh et al, 2018), Nigeria (3-11%) So et al, 2018), Burkina Faso (5%) (Miguel et al, 2017), Morocco (2%) (Miguel et al, 2017), and Pakistan (3%) . See Fig.…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 99%